2022
DOI: 10.1021/acsapm.2c00269
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Re-Entrant Honeycomb Polyurethane Aerogels

Abstract: In this work, polyurethane aerogels are fabricated in re-entrant honeycomb forms to achieve auxeticity and much higher flexibility than corresponding aerogel monoliths. For this purpose, a set of re-entrant honeycomb-shaped hollow molds is first printed from high-impact polystyrene (HIPS) using a fused filament fabrication technique and subsequently filled with polyurethane sol synthesized from an aliphatic triisocyanate and a diol selected from among butanediol, pentanediol, hexanediol, or octanediol. A sol–g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…[5][6][7] Therefore, polymer aerogels have garnered increasing attention because they have better mechanical properties, processability, and density than inorganic aerogels. [8][9][10][11] It is well known that the mechanical properties and thermostability of aerogels are related to not only their porous structure but also the intrinsic mechanical properties and heat resistance of the materials that make up the aerogels. Polymer aerogels typically operate at lower temperatures than inorganic aerogels because of the poor heat resistance of most polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Therefore, polymer aerogels have garnered increasing attention because they have better mechanical properties, processability, and density than inorganic aerogels. [8][9][10][11] It is well known that the mechanical properties and thermostability of aerogels are related to not only their porous structure but also the intrinsic mechanical properties and heat resistance of the materials that make up the aerogels. Polymer aerogels typically operate at lower temperatures than inorganic aerogels because of the poor heat resistance of most polymers.…”
Section: Introductionmentioning
confidence: 99%
“…5–7 Therefore, polymer aerogels have garnered increasing attention because they have better mechanical properties, processability, and density than inorganic aerogels. 8–11…”
Section: Introductionmentioning
confidence: 99%
“…To modify the inherent fragility of the aerogel, ductile polymers, such as poly­(vinyl alcohol) (PVA), , polyurethane (PU), and waterborne polyurethane (WPU), have also been introduced to the composite with rigid ANF networks within porous structures. Inspired by the concept of sustainable development, WPU, the aqueous dispersion of PU colloidal nanoparticles, is more and more used to replace the traditional solvent-borne PU products in various fields to reduce the emission of volatile organic compounds (VOCs). In addition, the relatively low viscosity of the dispersion significantly reduces the mixing difficulties with ANF. However, as a thermodynamically unstable dispersion, the spatial aggregation of the colloidal particles and the fractal geometry of the condensed network would be quite complex and highly dependent on the external factors triggering destabilization, i.e., the manner used to introduce the 1D nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Fonner and Jana also identified that poor flexibility of aerogels is a concern for handling of aerogel-coated fabrics as filter media and that not all fabric types can be considered. Recent studies used additive manufacturing tools to circumvent the poor flexibility of aerogels and reported fabrication of complex shape aerogel articles for applications in filtration and thermal insulation. Kulkarni et al recently reported fabrication of an aerogel filter medium using 3D printing for separation of water droplets from ultralow sulfur diesel fuel and observed an efficiency of up to 97% aided by size exclusion of water droplets by the small pores and adsorption of nonionic surfactants on polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%